Penelitian Pendahuluan Pengembangan Model Pembelajaran Berbasis Learning Management System (LMS) Pendekatan Saintifik untuk Menumbuhkan Kemandirian Belajar Mahasiswa - Sugiyono, Sugiyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Conventional learning that is too teacher-centered has an impact on the lack of development of student learning independence. This study analyzes the need for the importance of model development in learning. This type of quantitative descriptive research is in the Preliminary Study phase of the Plomp R&D model. The population is students at PTKI in East Kalimantan. Data collection through a survey of 87 respondents, interviews, and document studies which were analyzed descriptively quantitatively. The results showed that ongoing learning has not encouraged learning independence with the achievement level of respondents Strongly Agree 34.3%, Agree 31.7%, Disagree 26.3% and Disagree 7.7%, while on the aspect of using IT in learning respondents rate Strongly Agree by 35.4%, Agree 29.1%, Less Agree 27%, Disagree 8.4%. From the results of analysis and statistical tests obtained results of 0.2 > 0.05 (data normally distributed), linearity test results of 0.177 > 0.05, t test results 0.00 <0.05, validity test results on variables x,y > 0.2108, and reliability tests of 0.626> 0.600. It can be concluded that the development of an LMS-based learning model with a scientific approach to increase student learning independence is necessary and feasible to develop.